Sustainable Fertilization Strategy: The Effect of Mono Potassium Phosphate and Amino Acid Liquid Organic Fertilizer on Melon Plants - Rohcahyani, Fadilla Eka; Hidayat, Ramdan; Kusumaningrum, Nora Augustien (Universitas Panji Sakti, 2025)
Melon plants are a high-value horticultural commodity favored by consumers for their taste and market appeal. This study aimed to determine the best combination of Mono Potassium Phosphate (MKP) fertilizer and Amino Acid Liquid Organic Fertilizer (LOF) doses to enhance the growth and yield of melon plants while promoting nutrient balance and minimizing environmental impact. The experiment was conducted from April to July 2024 in a greenhouse located in Jatirejo Village, Nganjuk Regency, with LOF composition analysis carried out at the BSIP Laboratory. A factorial experiment using a Randomized Block Design (RBD) was applied with two factors: MKP fertilizer dose (5, 10, and 15 g/plant) and LOF dose (0, 50, 100, and 150 ml/plant), resulting in 12 treatment combinations replicated three times. Observed parameters included plant length, number of leaves, fruit weight, fruit diameter, and fruit length. Data were analyzed using ANOVA and followed by a 5% BNJ test for significant differences. The results showed a highly significant interaction between MKP and LOF treatments, with the combination of 15 g MKP and 100 ml LOF per plant producing the best outcomes across most growth and yield parameters, indicating that this treatment is optimal for maximizing melon productivity in a sustainable manner.